STRATEGI SALURAN DISTRIBUSI LAYANAN DI ERA DIGITAL: TINJAUAN LITERATUR SISTEMATIS ATAS STUDI TERINDEKS SCOPUS (2020-2026) - Sinarwaty; Wa Ode Nella Arnianti; Ninar Pratiwi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study compiles a systematic literature review of service distribution strategies by focusing on key elements such as service distribution channels, direct channels, electronic channels, channel selection, and the role of intermediaries. The dataset is built from a single Scopus query and exported in CSV format. After filtering by title, abstract, keywords, and source metadata, a total of 39 articles published in the period 2020 to 2026 were retained from the initial 72 recordings. This review combines descriptive mapping and qualitative thematic synthesis at the metadata and abstract levels. The findings suggest that the literature has shifted from isolated channel decisions to integrated service ecosystems, with five dominant themes: omnichannel and service distribution strategies, financial and banking services, healthcare and public services, tourism-culture-hospitality, and after-sales systems/products-services. Most studies are quantitative empirical or analytical model-based, while qualitative research and theory development are still limited. In various contexts, the most common explanatory mechanisms are the quality of channel integration, trust, technology acceptance, service coordination, and governance of digital and physical touchpoints. This synthesis shows that service distribution performance is no longer defined by reach or efficiency alone, but rather by how companies align direct, intermediary, and digital channels to create a seamless customer journey and a sustainable value proposition. This review contributes through a consolidated conceptual framework, a structured research map, and a practical agenda for service organizations designing channel architectures in the digital age. Since this review is based on metadata and abstracts of Scopus export results, future research needs to expand the analysis through full-text review and multidata base triangulation.